Evaluation of the Effect of Early-Onset Steroid Treatment in the COVID-19-Positive Pregnant Women on Pregnancy Outcomes - Neval Elgormus; Abdulhalim Senyigit; Omer Okuyan; Fatma Bozkurt; Derya Sivri Aydin; Hafize Uzun (Viruses)
Objective: Coronavirus disease 2019 (COVID-19) is the disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Acute respiratory distress and preterm delivery are the two major complications induced by SARS-CoV-2 infection during pregnancy. In the presence of dyspnea, the use of systemic corticosteroids was recommended in pregnant and non-pregnant groups. Our primary aim was to investigate the effect of early-onset steroid treatment on mortality and adverse effects in pregnant women with COVID-19. Our secondary aim was to investigate the effect of steroid treatment on the length of hospital stay and intensive care unit (ICU) stay, and duration of treatment. The study also investigated infection, preterm birth, and ideal body weight (lbw) in newborns. Methods: In this retrospective study, 253 patients were divided into three groups according to steroid administration. In Group 1 patients (n:112), treatment was started at the time of hospitalization. In Group 2 patients (n:90), treatment was started at least 24 h after hospitalization. Group 3 consisted of patients (n:51) who did not receive steroid treatment. Methylprednisolone (32 mg/day) was given to pregnant patients with a gestational age below 24 weeks or above 34 weeks, and dexametazone (6 mg/day) was given in four doses followed by 32 mg/day methylprednisolone for the others (whose baby was at a gestational age of 24 weeks and above but less than 34 weeks). Result: The hospital stay, ICU stay, and steroid administration time were significantly lower in the Group 1 when compared to the others (p < 0.05). The steroid treatment requirement was 4.4 days in Group 1 and 5.7 days in Group 2 (p < 0.05). While no death was observed in Group 1, one patient died in Group 2 and three patients died in Group 3. There was no difference between the groups in terms of complications, including preterm labor. Conclusions: No death was also observed with early-onset treatment. Early-onset treatment may be beneficial for fewer hospitalizations, fewer ICU stays, and less mechanical ventilation requirement in pregnant women with COVID-19. In addition, with early treatment, the total number of steroid administration days was reduced, which is important in terms of reducing the risk of side effects.